Permissive Hypotension Strategy in Open-surgery of Abdominal Aortic Aneurysm - Budiman, Alvian Chandra; Ganitafuri, Handayu; Putro, Bambang Novianto (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2023)
Background: Open-surgery in patients with aortic aneurysms has always been a challenge for every anesthesiologist. The risk of massive bleeding, hemodynamic instability, and peripheral perfusion insufficiency are some of the reasons for the need of appropriate perioperative management. The purpose of this case report is to describe the permissive hypotension strategy in open-surgery of abdominal aortic aneurysm. Case Ilustration: A 65-year-old man with radiologic findings of an aneurysm in the abdominal aorta at 3rd-4th lumbar vertebrae level was planned for open-surgery aneurysmectomy and aortic graft. Pre-operative assessment concluded the physical status of ASA III. Patient was planned to receive general anesthesia. Invasive hemodynamic monitoring was performed by placing an arterial line and a central venous catheter. Just before the aortic clamp procedure, permissive hypotension strategy was started by lowering systolic blood pressure using titrated doses of nitroglycerin with target MAP of >60 mmHg. Bleeding management was carried out with intravascular fluid resuscitation until the CVP target of 7-8 mmHg was achieved. When the aortic clamp was released, titrated dose of norepinephrine was administered with target MAP of 65-75 mmHg. Post-operatively, the patient was admitted to the ICU. The patient was discharged on the seventh post-operative day. Conclusion: This case demonstrated the successful perioperative management of an open surgery aneurysmectomy by maintaining the hemodynamic stability of the patient using permissive hypotension strategy. The successful stabilization of patient’s hemodynamic state during surgery resulted in a good and fast post-operative outcome and recovery.